2016
DOI: 10.1016/j.semarthrit.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of intra-articular saline as a comparator in clinical trials of knee osteoarthritis treatments: A systematic review and meta-analysis of randomized trials

Abstract: Pain relief observed with IA saline should prompt health care providers to consider the additional effectiveness of current IA treatments that use saline comparators in clinical studies, and challenges of identifying IA saline injection as a "placebo."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
3
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 69 publications
2
117
3
15
Order By: Relevance
“…In a systematic review and meta-analysis of 74 randomized clinical trials for the treatment of OAK with hyaluronic acid, it was concluded that saline has a “large placebo effect” of approximately 30% pain reduction [8]. Other meta-analyses of randomized controlled trials have demonstrated that the administration of IA saline significantly improves short-term (≤ 3 months) and long-term (6-12 months) knee pain, improves function, and decreases stiffness [9, 10]. Finally, in a systematic review of the literature for IA therapy in OAK [11], several studies demonstrate efficacy of a single saline injection or saline lavage in patients with OAK [12, 13].…”
Section: Analgesic Effects Of Salinementioning
confidence: 99%
“…In a systematic review and meta-analysis of 74 randomized clinical trials for the treatment of OAK with hyaluronic acid, it was concluded that saline has a “large placebo effect” of approximately 30% pain reduction [8]. Other meta-analyses of randomized controlled trials have demonstrated that the administration of IA saline significantly improves short-term (≤ 3 months) and long-term (6-12 months) knee pain, improves function, and decreases stiffness [9, 10]. Finally, in a systematic review of the literature for IA therapy in OAK [11], several studies demonstrate efficacy of a single saline injection or saline lavage in patients with OAK [12, 13].…”
Section: Analgesic Effects Of Salinementioning
confidence: 99%
“…Любопытной особенностью нашего исследования стало достаточно высокое терапевтическое действие ложной МТ. Следует уточнить, что значительный эффект плацебо при лечении ОА был отмечен рядом ведущих экспертов по этому заболеванию [18,19]. Так, по мнению W. Zhang, более 75% снижения боли, скованности и улучшения функции при лечении ОА (при использовании любых методов терапии) определяется плацебо-эффектом [20].…”
Section: Discussionunclassified
“…Most remarkably, the placebo effect was clinically meaningful (typically an improvement of two points on the 11-point pain scales) and sustained throughout the 24-week follow-up. Altman et al have recently undertaken a systematic review of the clinical benefit of IA saline in knee OA 23 . In both shortterm ( 3 months) and long-term (6e12 months) trials, IA saline provided significant improvement in knee pain, leading the authors to suggest that IA saline may provide a physiologic effect per se and is not a true placebo.…”
Section: Discussionmentioning
confidence: 99%